Energy-efficient base station placement and optimization in multi-hop wireless sensor network - Azamuddin, Ab Rahman; Hamim, Sakib Iqram; Noor Akma, Abu Bakar; Mohd Hafiz, Mohd Hassin (IEEE Xplore, 2025)
Wireless Sensor Networks (WSNs) architecture in Internet of Things (IoTs) consists of a collection of devices and networks varying in shape, size, compatibility, functionality, and complexity. Key characteristics of WSNs include energy efficiency, network lifetime, computing, and memory. Although a node communicates with another node or a Base Station (BS) through multi-hop information transfer, this process consumes significant time and energy. Consequently, nodes farthest from the BS deplete their energy quickly. To address this issue, the effect of BS placement along with energy efficiency is investigated. An algorithm for BS placement suited to a 2-Tier network environment has been improved, where one of the point locations is chosen as the optimal location. The BS moves to a new suitable position after several iterations, depending on the number of active nodes in the network. The proposed approach, Energy Efficient Cluster Head and Relay Node (EECR), demonstrates higher accuracy, lower energy consumption, and longer network longevity compared to Stable Election Protocol (SEP) and MultiTier Access Protocol (MAP). EECR produced better results by considering LND as the metric, with improvements of 27%,33%, and 43% in Scenarios 1, 2, and 3, respectively.